Pulmonary tuberculosis patients a wareness of their disease in the context of their knowledge and well-being - Metrikytė, Indrė; Gerikienė, Vitalija (Slauga. Mokslas ir praktika, 2020)
The aim of the study: to reveal the knowledge of patients with tuberculosis and their illness in the context of this disease. Material and methods. A Quantitative study was conducted on anonymous, questionnaire survey. The study was conducted at the Republican Siauliai County Hospital Tuberculosis and Lung Diseases Clinic. The obtained data were analyzed by SPSS17. The chi square criterion was used to calculate the significance level p. The difference in attributes is statistically significant when p ≤ 0.05. Conclusions. Most of the patients know the concept of tuberculosis and DOTS, pathogens, symptoms of the disease and diagnostic studies. Patients with this disease are feeling strong coughing, weakness and tiredness feeling every day. The disease becoming part of respondents’ life is related to their marital status (p<0.05). Usually the psychological assistance of the relatives reaches those respondents who have evaluated their knowledge satisfactorily and are lacking knowledge than those who evaluated their knowledge as well (p<0.05). According to the opinion of respondents, nurses are providing more knowledge about the disease to women than men (p<0.05).